THE RELATIONSHIP BETWEEN FOREIGN DIRECT INVESTMENT AND GROSS DOMESTIC PRODUCT IN INDONESIA - Sartika (NIM : 19009168), Alfiani
Indonesia is growing country that concern to its economic development. It has tried to develop since it first declared its independence. Since 1998, Indonesia had experienced many crisis. Some of crisis were crisis on 1998 and crisis on 2008. The reason why the crisis happened was caused by fund need from many sectors in Indonesia. On crisis 1998, the main reason that caused crisis was because leakage in private business sector of Indonesia that borrowed money from foreign investor and on crisis 2008, the main reason that caused crisis was because money withdrawal by foreign investor. All of the reasons were related to condition of foreign investment in Indonesia. Foreign direct investment is considered brings impact to economic development of Indonesia that is usually denominated by gross domestic product (GDP). Try to prove the relationship between foreign direct investment and gross domestic product of Indonesia is main objective in this research. This research talks about linear regression analysis between two variables. The two variables are FDI as independent variable and GDP as dependent variable. Used Gauss Markov assumptions helps in proving the validity of regression. It will show that the regression is BLUE that followed by some terminologies. The terminologies that pertains BLUE are heteroskedasticiy, autocorrelation, multicollinearity, and normal distribution. Computing the data by SPSS software supports analysis related to that BLUE. Baesd on T-test , it concludes to reject Ho that says FDI does not drive GDP. It does not reject Ha that says FDI drives GDP. It indicates from R Squared that 86.3% variance of Gross Domestic Product is affected by independent variable of FDI and there is stil 13.7% variance of Gross Domestic Product is affected by other independent variables. The assumptions of Gauss Markov that talks about heteroskedasticity, autocorrelation, multicolinearity and normal distribution have been covered and showed positive answer. F rom histogram, normal P-P Plot and scatterplot, it answered the assumptions that the errors of data have no autocorrelation, have fulfilled the heteroskedasticity, and have shown to be distributed well in normal distribution. Because this type of analysis is simple linear regression analysis, it does not related to multicolinearity. This results significantly proves that the regression is BLUE. By this depth analysis, it proves relationship between the independent variable FDI and the dependent variable GDP. Through positive relationship between FDI and GDP, future GDP condition in Indonesia could be predicted by past FDI condition in Indonesia. It is hoped that this can bring knowledge for better understanding about economic condition in Indonesia. Keyword: Foreign Direct Investment, Gross Domestic Product